Using HTA and guideline development as a tool for research priority setting the NICE way: reducing research waste by identifying the right research to fund. Issue 3 (8th March 2018) - Sharma, Tarang; Choudhury, Moni; Rejón-Parrilla, Juan Carlos; Jonsson, Pall; Garner, Sarah
Abstract : Background: The National Institute for Health and Care Excellence (NICE) was established in 1999 and provides national guidance and advice to improve health and social care. Several steps in the research cycle have been identified that can support the reduction of waste that occurs in biomedical research. The first step in the process is ensuring appropriate research priority setting occurs so only the questions that are needed to fill existing gaps in the evidence are funded. This paper summarises the research priority setting processes at NICE. Methods: NICE uses its guidance production processes to identify and prioritise research questions through systematic reviews, economic analyses and stakeholder consultations and then highlights those priorities by engagement with the research community. NICE also highlights its methodological areas for research to ensure the appropriate development and growth of the evidence landscape. Results: NICE has prioritised research questions through its guidance production and methodological work and has successfully had several research products funded through the National Institute for Health Research and Medical Research Council. This paper summarises those activities and results. Conclusions: This activity of NICE therefore reduces research waste by ensuring that the research it recommends has been systematically prioritised through evidence reviews and stakeholder input.